2013
DOI: 10.1039/c2lc40845g
|View full text |Cite
|
Sign up to set email alerts
|

NutriChip: nutrition analysis meets microfluidics

Abstract: This focus article introduces the concept of NutriChip, an integrated microfluidic platform for investigating the potential of the immuno-modulatory function of dairy food. The core component of the NutriChip is a miniaturized artificial human gastrointestinal tract (GIT), which consists of a confluent layer of epithelial cells separated from a co-culture of immune cells by a permeable membrane. This setting creates conditions mimicking the human GIT and allows studying processes that characterize the passage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 38 publications
1
86
0
Order By: Relevance
“…Higher Lucifer yellow permeability has been described for the same cell type cultured in a microfluidic chamber, but that system did not allow measurement of TEER [30]. Note that Caco-2 cells in a gut-on-a-chip model have reached tighter barrier properties when co-cultured with bacteria and/or immune cells, and exposed to low shear stress and cyclic strain to mimic peristaltic motion [4,32].…”
Section: Intestinal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher Lucifer yellow permeability has been described for the same cell type cultured in a microfluidic chamber, but that system did not allow measurement of TEER [30]. Note that Caco-2 cells in a gut-on-a-chip model have reached tighter barrier properties when co-cultured with bacteria and/or immune cells, and exposed to low shear stress and cyclic strain to mimic peristaltic motion [4,32].…”
Section: Intestinal Modelmentioning
confidence: 99%
“…Confluent monolayers of adherent epithelial or endothelial cells grown on culture inserts are widely used static models for intestinal, lung and blood-brain barriers (BBB). The Caco-2 human epithelial cell line is a well characterized model of the intestinal barrier applied for screening of drug candidates [3][4][5][6]. Several studies describe the lung epithelial cell line A549 as a model of the lung barrier [7,8].…”
mentioning
confidence: 99%
“…17 Multichamber MPS devices have been developed 121 specifically to study the activation of immune cells by the transfer of nutrients across the gastrointestinal epithelium. 122 The ability to study intestinal flora in MPS has already been demonstrated. 67 But the GI tract is also an entry point for pathogens.…”
Section: Mps Immunologymentioning
confidence: 99%
“…Calibration lines and system validation were performed on U937 cell line for both glucose and lactate detection. U937 are hystiocytic lymphoma cells that can differentiate into macrophagelike cells under certain treatments (Ramadan et al, 2013). Many laboratory models investigate the transport of molecules through the epithelial barrier of the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%